Application of evolutionary algorithms for the model-free determination of scattering matrix and the numerical diagonalization of Nilsson-model Hamiltonian - Vodin, A.N.; Korda, V.Yu.; Dovbnya, A.N.; Molev, A.S.; Korda, L.P. (Вопросы атомной науки и техники, 2004)
A new model-free approach for analyzing the intermediate-energy light nucleus-nucleus elastic-scattering differential cross-sections is proposed to extract the numerical dependencies of S-matrix modulus and nuclear phase on angular momentum directly from the experimental data via the evolutionary algorithm. The refractive and absorptive properties of the ¹⁶О – ¹⁶О-interaction at Е = 22…44 МeV/nucleon are studied. The new approach based on a genetic algorithm is presented to diagonalize the Hamiltonian matrix of the Nilsson-model for the deformed axially symmetric nucleus. The tests witness that the larger the matrix size the more effective the genetic approach becomes comparing to the traditional diagonalization methods.